MODERN ASPECTS OF ALLERGIC RHINITIS PHARMACOEPIDEMIOLOGY IN CHILDREN - N.V. Malyuzhinskaya; I.N. Shishimorov; A.V. Razvalyaeva; A.V. Shatalin (Педиатрическая фармакология, 2009)
The article provides the authors’ proprietary data on the epidemiology of allergic rhinitis, as well as the results of assessing the adequacy of existing approaches to diagnostics, monitoring and treatment of children in Volgograd. A retrospective descriptive research was conducted using the data of 330 outpatient medical records of children aged 1 to 16 years diagnosed with allergic rhinitis. Analysis was made of the age at which the disease was verified, the diagnosis formulation, family medical history, related allergic diseases, therapeutic and diagnostic tactics. It was found that an average of 5,5 years elapse from the time the symptoms are identified to the time a diagnosis is made. 21% of children have first symptoms of the disease already at an early age (prior to 3 years). 71% of children had it in combination with other allergic diseases. Second-generation antihistamines are now increasingly used for treatment of allergic rhinitis, while intranasal corticosteroids are still not used frequently enough.Key words: pharmacoepidemiology, epidemiology, allergic rhinitis, bronchial asthma, children.